An improved scheme for data hiding in encrypted H.264/AVC videos - Xu, Dawen; Wang, Rangding; Shi, Yun Q. (Journal of visual communication and image representation, 2016)
•The embedding is done on encrypted H.264/AVC data without knowing the decryption key.•The paired code-word substitution and multiple-base notational system are exploited.•Both encryption and data embedding keep the bit-rate intact.•Data extraction can be carried out either in encrypted or decrypted domain. Recently, a novel scheme to hide data into encrypted H.264/AVC videos using code-word substitution has been proposed by Xu et al. However, the statistical analysis of CAVLC code-words demonstrate that Xu et al.’s work does not fully exploit redundancy existing in CAVLC code-word for data embedding. In this paper, an improved version of Xu et al.’s data hiding method in encrypted H.264/AVC videos is proposed. Specifically, when suffixLength is equal to 1, data embedding is performed by paired code-word substitution. When suffixLength is greater than 2, not the single code-word substitution but the multiple-based notational system is adopted for data embedding. Experimental results have demonstrated that the improved method is indeed capable of providing a larger embedding capacity in comparison with Xu et al.’s method. Moreover, both encryption and data embedding can be accomplished without affecting the coding efficiency of H.264/AVC by keeping exactly the same bitrate.